A cross sectional study on morbidity pattern in two primary health centers of Bishnupur District, Manipur - Sonarjit Singh, Khangembam; Laisram, Micky Singh; Thangjam, Gayatri; Singh, T. Gambhir (International Journal Of Community Medicine And Public Health, 2023)
Background: PHCs and PHSCs are the grass-root level of the health care system of India which deals directly with the majority of the population as they live in rural areas and have no access to proper health care systems. This study was conducted due to the scarcity of studies and limited health care services amongst people in rural populations of Manipur to determine the morbidity pattern of patients attending OPD in 2 PHCs of Bishnupur District under RHTC, RIMS, Imphal, Manipur for the year 2021. Methods: A cross-sectional study based on previous records was conducted from 1 January to 31 December 2021 among the newly registered outpatients attending the OPD of Oinam and Leimapokpam PHCs in Bishnupur District. Secondary data from the two PHCs were collected. Data analysis was done by using SPSS software version 21. Results: The study found that almost half (46.4%) of patients attending OPD are 15-49 years followed by <15 years (38.7%). Out of total morbidity, respiratory diseases (24.8%) followed by GIT (15.9%), OBG, skin diseases and NCD constitute major morbidity among the study population. Conclusions: The study gives an outline of the morbidity pattern of patients attending OPD in two PHCs of the Bishnupur district in one year which could help healthcare providers and administrators to plan, practice and deliver quality services as per community needs.